1996
DOI: 10.1007/bf00353924
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved carbon dioxide accumulation in a large scale and high density production of TGF? receptor with baculovirus infected Sf-9 cells

Abstract: Production of a TGFβ receptor with high density baculovirus infected Sf-9 cells (7×10(6)cells ml(-1)) served as a test run for a retrofitted 150 L microbial fermentor. The entire 110 L batch run was performed in serum free medium, with an addition of a concentrated amino acid and yeastolate mixture at the time of infection. This addition strategy has been proven effective at a small scale by enabling cultures to maintain maximum product yield. In the bioreactor however, while cellular growth was comparable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 17 publications
1
32
1
Order By: Relevance
“…This value was used as an indicator of the volumetric oxygen consumption. The overall aeration strategy was similar to what has been described earlier by our group [34].…”
Section: Bioreactor Culturesmentioning
confidence: 79%
“…This value was used as an indicator of the volumetric oxygen consumption. The overall aeration strategy was similar to what has been described earlier by our group [34].…”
Section: Bioreactor Culturesmentioning
confidence: 79%
“…If a low enriched air flow rate or pure oxygen are used to enhance the driving force and thereby reduce the flow rate and potential for damage due to bursting bubbles, high levels of pCO 2 of 150-200 mm Hg are predicted to be reached (Gray et al 1996) and such levels have been measured in 1800-2500 L bioreactors and a high cell density perfusion bioreactor (Gray et al 1996;de Zengotita et al 2002). Detrimental effects have been reported for growth and productivity of a recombinant myeloma process (Aunins et al 1993), hybridoma, NSO, BHK, (de Zengotita et al 2002, CHO (Gray et al 1996;Mostafa and Gu 2003) and insect cells (Garnier et al 1996) at these high levels of pCO 2 , though these cells grew well in the rangẽ 35 to~80 mm Hg pCO 2 , comparable to the physiological range of 31-54 mm Hg pCO 2 (de Zengotita et al 2002).…”
Section: Carbon Dioxide/osmolalitymentioning
confidence: 99%
“…Overall, Mostafa and Gu (2003) reported an improved productivity (40%), culture time (the fed-batch time was extended from 10 to 14 days) and final titre (2-fold, equivalent to that at the 1.5 L scale). However, they also noted that at constant pH, higher pCO 2 is also associated with higher osmolality and that therefore the improved performance at lower pCO 2 might also be due to reduced osmolality (Garnier et al 1996;de Zengotita et al 2002) but it was not monitored. In passing, it should be mentioned that the use of antifoam enabled the use of higher air flow rates (0.004 vvm) with the sparge stone without excessive foaming and again enabled the culture duration to be extended from 10 to 14 days (Mostafa and Gu 2003).…”
Section: Carbon Dioxide/osmolalitymentioning
confidence: 99%
“…Kunkel et al reported that reduction in dissolved oxygen caused decreased glycosylation of antibody N-glycan chains. 65 Dissolved CO 2 is also an important process variable because it can accumulate to inhibitory levels at values greater than 120-150 mm Hg [66][67][68] and affects product quality. Even though dissolved CO 2 sensors are commercially available, e.g., from YSI Inc., (Yellow Springs, OH) or Metler Toledo (Columbus, OH), dissolved CO 2 is still measured using off-line blood gas analyzers such as those from Nova Biomedical (Waltham, MA).…”
Section: -61mentioning
confidence: 99%